Does Motivational Training Based on Self-Potential Development Improve the Students' Social Entrepreneurship Intention? - Widiyanto Widiyanto; Ahmad Jaenudin; Muhammad Feriady; Kusumantoro Kusumantoro (Economics Education Department Universitas Negeri Semarang, 2025)
The number of pesantren in Indonesia is vast and has contributed to economic development and growth. The development of pesantren today is about providing entrepreneurial provisions for students (santri) so that they will be ready to enter the community by having the ability to act creatively and innovatively. This research intends to strengthen students' social entrepreneurship intentions by applying motivational training based on developing self-potential. The research to be carried out is experimental research with quasi-experimental research techniques (quasi-experimental design). The research was conducted at the Pondok Pesantren as Salafy Al Asror, Semarang City, Central Java, Indonesia. The data collection techniques used are tests, observations, and interviews. The results indicated that managerial ability, motivational ability, creativity, and communication significantly affect the intention of the student to pursue social entrepreneurship. This research also develops an entrepreneurial model for students by utilizing the abilities possessed by students, namely managerial abilities, motivation, creativity, and communication. The model developed was tested differently and, based on the model developed, was effective in increasing the intention of students to pursue social entrepreneurship. Thus, this research has contributed to creating social enterprise intentions in students through the students' self-potential.